Avaliação da ação sanitizante do ácido peracético em peças de carne bovina - Pereira, Tafael Lucas (2015)
The primary responsibility for the safety and quality of food are of those who produce, process and market. Multiple intervention strategies have been developed to reduce the level of microorganism in beef, such as salts with acids and sanitization. Assuming the goal is to evaluate the sanitizing action of peracetic acid in beef duckling (Vastus lateralis) obtained refrigerators with separate quality system. The peracetic acid is characterized by a very fast action and antimicrobial activity of broad spectrum, and that its decomposition generates biodegradable and non-toxic byproducts. The experiment was divided into two stages, the first stage was carried out to determine the effectiveness of peracetic acid at different concentrations of microorganisms involved in the refrigerator production process. The second step is the application of peracetic acid in the specified concentration as effective for the experiment derived from refrigerators parts with distinct inspection system (State and Federal), as well as in parts artificially contaminated with coliforms thermotolerant. According to the study results, only the microorganisms from the group of coliforms (total and thermotolerant) had an inhibition to the application of peracetic acid. The concentration that showed the best performance in inhibiting microorganisms was studied concentration of 1%, lower values than the control sample. It can be seen to the study, that the application of peracetic acid in bovine duckling parts for control of thermotolerant coliforms, it is an alternative easy, fast and with satisfactory results. The application of sanitizer in artificially contaminated parts reduced contamination in 3 log cycles. For the tests in inspection systems, the values of the sanitized parts are smaller and more stable than the control sample. According to the technological standards, the pH and acidity are within the standard established in the literature for human consumption, because, with the color analysis were identified change due account of the sanitation procedure, but it is emphasized that the sanitized samples showed red color values greater than the control sample. That said, the application of peracetic acid is not to be considered as a corrective action of the production process but as a preventive action to integrate the joint quality tools deployed for product quality assurance.